The Province of the Rule of Law (Finally) Determined - Del GRANADO, Juan Javier; BULL, Jesse (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019, 2019)
Under the general assumptions of democratic theory, legislatures have positive legitimacy to make law because of the power of the people who elected them. Throughout the world, however, unelected judges also make law. What, if anything, gives such judges positive legitimacy to make law? This paper demonstrates, through two superficially simple game-theoretic examples, that judges’ positive legitimacy is based on the power of people. Courts' legitimacy has the same basis as legislatures'. Since the French revolution, the ultimate arbiter in the social fight is the strongest faction, the majority. A group of people communicates its type to society at the ballot box. Based on the ballot count, society makes concessions to the terms dictated by the majority. Under what circumstances would an individual ever be able to dictate terms to society? This paper demonstrates that the court system allows a single individual to act collectively with other similarly situated individuals spread out through time. This paper argues that this group can communicate its type to society through legal reasoning. Courts are insulated from the political process because unelected judges are supposed to be beholden to a temporally disconnected group, rather than to contemporaneous constituencies.